Financial Literacy Factors And Financial Attitudes In Influencing Student Financial Behavior - Hani Fitria Rahmani; Delina Herdian Septiani; Muhammad Alam Mauludina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The financial behavior of students shows a tendency toward consumption, leading to poor financial management. This study aims to analyze the influence of financial literacy and financial attitudes on the financial behavior of accounting students at IPB University. A quantitative method with descriptive and associative approaches was employed. A sample of 74 active students was selected using purposive sampling. The results show that both financial literacy and financial attitudes have significant partial and simultaneous effects on financial behavior. Financial literacy contributes 49.5% and financial attitude 24.9%, with both explaining 74.4% of behavioral variance. These findings emphasize the importance of integrating financial knowledge and attitudes to foster responsible financial behavior. The findings imply the need for structured financial literacy curriculum and programs aimed at developing positive financial attitudes in higher education.